2013
DOI: 10.1038/nm.3290
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous PET-MRI reveals brain function in activated and resting state on metabolic, hemodynamic and multiple temporal scales

Abstract: Combined positron emission tomography (PET) and magnetic resonance imaging (MRI) is a new tool to study functional processes in the brain. Here we study brain function in response to a barrel-field stimulus simultaneously using PET, which traces changes in glucose metabolism on a slow time scale, and functional MRI (fMRI), which assesses fast vascular and oxygenation changes during activation. We found spatial and quantitative discrepancies between the PET and the fMRI activation data. The functional connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
178
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(193 citation statements)
references
References 27 publications
14
178
0
1
Order By: Relevance
“…Distinct replicable topographies were identified that are also physiologically different in regard to task-related network activation responses including NL1-PC1 deactivated by task and NL1-PC2 and NL1-PC3 activated by task. A recent experimental rat study demonstrated the presence of several similar network topographies in healthy animals scanned simultaneously with FDG PET and fMRI (34). Analogous covariance patterns have also been reported following the application of ICA to imaging data from healthy human subjects scanned in the resting state with both modalities (10).…”
Section: Discussionmentioning
confidence: 74%
“…Distinct replicable topographies were identified that are also physiologically different in regard to task-related network activation responses including NL1-PC1 deactivated by task and NL1-PC2 and NL1-PC3 activated by task. A recent experimental rat study demonstrated the presence of several similar network topographies in healthy animals scanned simultaneously with FDG PET and fMRI (34). Analogous covariance patterns have also been reported following the application of ICA to imaging data from healthy human subjects scanned in the resting state with both modalities (10).…”
Section: Discussionmentioning
confidence: 74%
“…PET/MR imaging was first applied in oncology (5) and neurology (3,7,10). With the recent arrival of integrated human PET/MR imaging scanners, clinical scientists are establishing new protocols for imaging, pushing PET/MR imaging to the forefront of advanced nuclear medicine, radiologic diagnostics, and staging (11).…”
Section: Preclinical Pet/mr Imaging In Oncologymentioning
confidence: 99%
“…First, in vivo preclinical and clinical studies impressively show the power of this new imaging device, which without doubt will cause a paradigm shift in the realm of imaging science (2,3,(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Functional MRI (fMRI), is used to assesses at the same time fast vascular and oxygenation changes during activation. These results demonstrate the feasibility of combined PET-MRI for the simultaneous study of the brain at activation and rest, revealing comprehensive and complementary information to further decode brain function and brain networks (Wehrl et al, 2013).…”
Section: How It Is Measured or Detectedmentioning
confidence: 68%